Pengaruh Asupan Gizi Dan Intensitas Olahraga Terhadap Kebugaran Fisik - Nimrot Manalu; Miftahul Ihsan; Andes Martua; Evelyn Brahmana; Andrey Simarmata; Limsar Hutabarat; Andre Nainggolan; Frengki Sihombing (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effect of nutritional intake and exercise intensity on physical fitness levels. The research method used was an experiment involving 120 respondents who were divided into three groups based on exercise intensity: light, moderate, and heavy. Data were collected through dietary questionnaires, physical fitness measurements, and interviews about exercise habits. The results showed that individuals with balanced nutritional intake and moderate to high intensity exercise had better physical fitness levels compared to those who did not maintain a diet and rarely exercised. In conclusion, the combination of good nutrition and regular exercise contributes positively to physical fitness.